Apelin (APLN) and Apelin Receptor (APLNR) in Human Ovary: Expression, Signaling, and Regulation of Steroidogenesis in Primary Human Luteinized Granulosa Cells. Issue 5 (1st November 2016) - Roche, Jennifer; Ramé, Christelle; Reverchon, Maxime; Mellouk, Namya; Cornuau, Marion; Guerif, Fabrice; Froment, Pascal; Dupont, Joëlle
Abstract: Apelin (APLN) is a recently discovered adipokine involved in the regulation of various metabolic functions. Its receptor, APLNR, is expressed in reproductive tissues, however, its role in human ovarian cells is unknown. In this study, we identified APLN and APLNR in human ovarian follicles and analyzed their expression in granulosa cells and follicular fluid obtained from obese and nonobese patients, with or without polycystic ovary syndrome (PCOS). We also investigated the effect of APLN on steroidogenesis in cultured human luteinized granulosa cells (hGCs) from nonobese patients without PCOS. Using RT-PCR and immunoblotting, we found that APLN and APLNR were expressed in hGCs and cumulus and theca cells. We confirmed these data immunohistochemically and observed that APLNR and APLN are present in human oocytes at different stages of follicular development. In patients with PCOS, we observed that follicular fluid APLN concentration and granulosa cell APLN and APLNR mRNA expression was higher than that observed in control patients. In cultured hGCs from nonobese patients without PCOS, insulin-like growth factor 1 (IGF1) increased APLNR expression, and recombinant human APLN (APLN-13 and APLN-17) increased both basal and IGF1-induced steroid secretion. These effects on steroid production were reversed when cultured in the presence of ML221, an APLNR antagonist, which was associated with an increased 3beta-hydrosteroid dehydrogenase (HSD3B) protein concentration. We showed that these effects were dependent on the activation of the AKT and MAPK3/1 pathways using pharmacological inhibitors. Our results show that APLN and APLNR are present in human ovarian cells and APLN increases IGF1-induced steroidogenesis in granulosa cells through an increase in HSD3B protein expression and activation of the MAPK3/1 and Akt pathways. Therefore, APLN and APLNR may play a role in human follicular development and the pathogenesis of PCOS.